Thyrotoxic Hypokalemic Periodic Paralysis – A Case Report - Prasad, Krishna G; Abraham, Lissa (Indian Journal of Case Reports, 2015)
Thyrotoxic hypokalemic periodic paralysis is a medical emergency which presents with muscular weakness, hypokalemia and features of thyrotoxicosis. Urgent treatment is very important; since, very low potassium levels can lead to cardiaccomplications. Here, we present a case where features of hyperthyroidism were missed on initial assessment and were picked up subsequently in the second presentation of paralysis. This emphasizes the importance in recognizing the subtle features of hyperthyroidism from both history and clinical examination. Acute management consisted of administering intravenous potassium chloride and then treatment of thyrotoxicosis.